Two Closely Related Env Antigens from the Same Patient Elicited Different Spectra of Neutralizing Antibodies against Heterologous HIV-1 Isolates - Vaine, Michael; Dueñas Decamp, María José; Peters, Paul; Liu, Qin; Arthos, James; Wang, Shixia; Clapham, Paul; Lu, Shan (My University, 2011)
Identification of immunogens capable of eliciting broadly neutralizing antibody (NAb) responses against HIV-1 is a major goal toward the development of an AIDS vaccine. Despite significant progress in understanding the structural features of the HIV-1 envelope glycoprotein (Env) and the discovery of multiple broadly neutralizing monoclonal antibodies with defined antigenic structures, the design of optimal Env immunogens to elicit broad NAbs remains a major challenge. As the structural determinants of Env immunogenicity remain unclear, we assessed two closely related Env antigens isolated from the same HIV-1-infected patient with different phenotypic features to identify what may result in a favorable immunogenic profile. One Env, B33, isolated from brain, was highly macrophage tropic with a high CD4 affinity, while the other, LN40, isolated from the lymph nodes, was poorly macrophage tropic with a low CD4 affinity. Using a DNA prime-protein boost approach, rabbits primed with LN40 Env antigen had a NAb response against heterologous primary isolates, while B33 Env antigens were capable of eliciting NAbs against only homologous and sensitive viral isolates. Further analysis revealed that the specificity of NAbs elicited by the LN40 antigen mapped to limited residues within or flanking the CD4 binding site. Certain key structural determinants were identified that could differentiate primary Env immunogens based on their potential to elicit broader NAbs. This progress will facilitate the rational design of effective HIV-1 vaccine formulations with optimal Env antigens.